Review of Useful Theories for Working with People Who are Living with HIV and AIDS - E.E, Enwereji,; R.A., Eke, (Journal of Clinical Research In HIV AIDS And Prevention, 2016)
Introduction Working with people who are HIV positive is a herculean task and relevant theories to assist them medically, psychologically, economically, socially and otherwise are necessary. People who are living positively with HIV and AIDS are usually ridiculed, discriminated against, rejected and isolated. Using theories to work with them will help to cushion the negative impacts of HIV and AIDS, especially stigma which has been identified as a major barrier to health care and quality of life in illness management. The fundamental human rights of people living positively with HIV and AIDS should be protected since majority of such rights are usually trampled upon. The review aimed at discussing the potential benefits of using theories to assist people living positively with HIV and AIDS to cope with their various and varying situations in life. Materials and Method: Information for this study was collected by extensive review of recent literature on theories for assisting people living positively with HIV and AIDS. The paper reviews theories that influence long-term behaviour change among people living positively with HIV and AIDS. It assesses the need for using these theories to improve HIV and AIDS intervention in developing countries including Nigeria. In this study, eleven behaviour theories were reviewed. Result It was noted that some of the theories promoted adherence as well as helped to explain the benefits of adherence to HIV and AIDS medication. Also a good number of the theories assisted researchers in designing effective intervention strategies. Conclusion: Further research is needed to determine the effective theories that will increase adherence to long-term treatment regimens of HIV and AIDS. Such theories can be used to alleviate the potential burnout of Caregivers and people living positively with HIV and AIDS who travel long distances for diagnostic procedures and work long hours without adequate remuneration, support and supervision.
Keywords: diagnostic procedures; HIV and AIDS; theories; perspectives; burnout